A portable SERS sensing platform for the multiplex identification and quantification of pesticide residues on plant leaves. Issue 36 (31st August 2022) - Ye, Cheng; He, Meng; Zhu, Zhengdong; Shi, Xiaoyi; Zhang, Maofeng; Bao, Zhiyong; Huang, Youju; Jiang, Changlong; Li, Jianhua; Wu, Yucheng
Abstract : The synergetic effect of the ZnO@Co3 O4 and the plasmonic AgNPs together with the molecular preconcentration enabled it to ultrasensitively and quantitatively detect organophosphorus pesticides on real samples on a portable Raman instrument. Abstract : The rapid identification and quantitative detection of organophosphorus pesticides on a portable device is of vital importance for food safety evaluation and human health protection. However, conventional strategies for realizing the reliable, portable and sensitive detection of target analytes are still challenging. Here, a novel dual-MOF-induced ZnO@Co3 O4 heterostructure modified with AgNPs was designed and fabricated as a surface-enhanced Raman scattering (SERS) sensor for the sensitive identification and quantitative analysis of organophosphorus pesticides. The ZnO@Co3 O4 heterojunction induced charge transfer enhancement in ZnO@Co3 O4 @Ag and achieved a 6.6-fold signal amplification compared to that of ZnO@Ag. The synergetic effect of the ZnO@Co3 O4 heterostructure and the plasmonic AgNPs together with the molecular preconcentration of the porous structure enabled it to ultrasensitively detect triazophos (10 −9 M), fonofos (10 −8 M) and thiram (10 −7 M) even on a portable Raman instrument. The SERS sensor exhibited superior signal reproducibility with an RSD value less than 8% and long-term stability with a signal loss of only 8.9% after 30 days. Moreover, this SERS platform provided the rapid quantitative analysis of triazophos, fonofos and thiram residues on real samples of tea and dendrobium leaves with LOD values of 10 −7 M, 10 −6 M and 10 −6 M, respectively. In addition, the multiplex detection of pesticides was realized, indicating that our strategy has great potential for quantitative pesticide residue analysis in real samples.